The Water Quality Analysis of Sustainable Seawater Desalination System using Ultrafiltration - QASDINA NAQIYAH BINTI MOHD KAMARUL HISYAM; NURSHUHAILA MOHAMED SUNAR (Progress in Engineering Application and Technology, 2025)
Freshwater scarcity is a growing global issue intensified by population growth, urbanization, and climate change. This study focuses on the development and evaluation of a compact and energy-efficient seawater desalination system that integrates ultrafiltration and reverse osmosis technologies. The system was designed to address diverse environmental conditions while ensuring high-quality freshwater production in compliance with Malaysian Water Quality Standards.  The desalination system achieved significant improvements in water quality, reducing salinity from 8.33 g/L to 0.27 g/L, TDS from 7216 mg/L to 286 mg/L, and stabilizing pH at 7.99. Ultrafiltration effectively removed large particles, microorganisms, and organic contaminants, minimizing fouling and extending the lifespan of reverse osmosis membranes. This multi-stage approach proved critical in achieving sustainable and efficient desalination performance. With its compact design, energy efficiency, and adaptability, the system is particularly suitable for applications in disaster relief, remote areas, and off-grid locations. By demonstrating the feasibility of producing high-quality freshwater with minimal environmental impact, this research highlights the potential of integrated filtration technologies as scalable and eco-friendly solutions to mitigate global freshwater scarcity.